Immature teratoma at umbilicus region presenting as exomphalos: A case report with review of literature - Lakshmi V Chavali; R Vijaya Bhaskar; J Bhaskar Reddy (Indian Journal of Medical and Paediatric Oncology)
Umbilical cord neoplasms are rare. Teratomas, which are accepted as the only true neoplasms at this site, are exceptional. These tumors are polymorphic in their presentation and are often associated with other abnormalities, with exomphalos being the most common abnormality. Histologically these tumors show mature tissues from all the three-germ layers. Immature elements as seen in our case are rare. Germ cells which have gone astray during embryonic development are thought to be the cells of origin of these tumors.